Transformasi Kepemimpinan dalam Manajemen Pendidikan Islam Era Digital: Studi Kasus di MA Al-Khoirot Putri - Alfin Nuris Sa’adah; Muhammad Husni (Jurnal Wahana Literasi Pendidikan, 2026)
Leadership transformation in Islamic educational management is a crucial phenomenon in the digital era, requiring a paradigm shift from traditional leadership models to adaptive and visionary approaches. This article aims to describe the essence of leadership from an Islamic perspective, identify leadership challenges in the digital era, and formulate innovative strategies to improve the quality of Islamic education. This study employs a descriptive qualitative approach with a case study conducted at MA Al-Khoirot Putri. Data were collected through an analysis of Islamic educational management literature contextualized with observations of leadership dynamics within the institution. The findings reveal that the essence of Islamic leadership lies in trustworthiness (amanah) and service, emphasizing exemplary conduct (uswah) and influence. In the digital era, leadership at MA Al-Khoirot Putri faces significant challenges, including gaps in technological literacy, differences in digital culture across generations, and the necessity of maintaining ethical technology utilization in accordance with Sharia values. Effective strategies that can be implemented include developing a digital mindset, strengthening technological competencies through collaborative training, and adopting a participatory leadership style tailored to the needs of the team. In conclusion, the integration of prophetic values and advancements in information technology serves as a key factor for leaders at MA Al-Khoirot Putri in producing competent graduates without compromising their religious identity.